THE EFFECT OF WORK ETHICS AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE AT THE OFFICE OF THE MINISTRY OF RELIGION DIVISION OF HAJJ AND UMROH SOUTH TANGERANG CITY - Asridah Warni Tanjung; Ading Sunarto (Yayasan Education and Social Center, 2023)
This study aimed to determine how much influence work ethic and discipline have on employee performance at the Office of the Ministry of Religion of the Hajj and Umrah Division, South Tangerang City. The method used in this study is quantitative analysis with a population of employees of the Office of the Ministry of Religion of the Hajj and Umrah Division of South Tangerang City, with as many as 60 respondents or with a sample of data collection techniques by distributing questionnaires. Data analysis methods used in this study were (validity test, reliability test and, classical assumption test), quantitative descriptive analysis, simple and multiple regression analysis, and analysis of the correlation coefficient and determination, hypothesis testing (T and F test). The results of the work ethic variable have a tcount value greater than ttable (3.847> 1.672) and a significant value less than 0.05 (0.000 <0.05). The results of the work discipline variable research. (F test). The results of this study showed that the Fcount value was 62.335, greater than the Ftable of 3.16 (62.335 > 3.16), and the significance value of 0.000 was less than 0.05 (0.000 <0.05). Work ethic and discipline positively influence and are significant in employee performance at the Office of the Ministry of Religion of the Division of Hajj and Umrah in South Tangerang City by 0.675 or 67.5%. In comparison, the remaining is 0.325 or 32.5%.